the Effect of Free Cash Flow Agency Problem on Stock Returns Synchronicity and Financial Reporting Quality - Shadi Jandaghyan; Shadi Jandaghyan (مطالعات تجربی حسابداری مالی, 2016)
Financial reports are tools that transfer accounting information to users,particularly investors. When the reporting quality is poor, investors rely on industry and market-level information. This action contributes to greater stock return movement with market and industry return, and Increases stock return synchronicity. Factors such as free cash flow agency problem may cause distortion of information quality by managers as a result outsider investors are misled. The purpose of this study is to investigate the effects of free cash flow agency problem on stock return synchronicity and financial reporting quality. In order to test the hypotheses, data of 105 firms listed in Tehran Stock Exchange during the years 1388 to 1392 were used. Findings of research signify that companies with strong free cash flow agency problem have a greater stock return synchronicity. Results also indicate that free cash flow agency problem has a significant and negative impact on the financial reporting quality. Thus investors who invest in the stock exchange and their main attention is focused on free cash flow, must to consider free cash flow agency problem as a factor affecting decisions.